2021
DOI: 10.1094/pdis-11-20-2329-re
|View full text |Cite
|
Sign up to set email alerts
|

Stemphylium Leaf Blight of Welsh Onion (Allium fistulosum): An Emerging Disease in Sanxing, Taiwan

Abstract: Welsh onion (Allium fistulosum L.) is one of the main and oldest vegetable crops grown in Taiwan. A severe epidemic of leaf blight in Welsh onion caused by a Stemphylium-like pathogen was found in Sanxing, Taiwan, from 2018 to 2020. However, correct species identification, biology and control of Stemphylium leaf blight (SLB) of Welsh onion is not well established. Therefore, the main objective of this study was to investigate the causal agent of SLB in Sanxing and evaluate the in vitro sensitivity of Stemphyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Studies showed that the maximum damage to onion stemphiliosis was observed in 2021, which was characterised by high humidity, heavy precipitation, and elevated air temperature. These results are consistent with previous experiments conducted by various authors using onion cultures (Wang et al, 2021;Wright et al, 2019). Gossen et al (2021) identified that the first symptoms of onion stemphiliosis coincided with the appearance of a large number of conidia, precipitation, leaf moisture duration of ≥8 hours, and days with an average daily temperature of ≥18°C.…”
Section: Source: Mycobank Database 2022supporting
confidence: 92%
“…Studies showed that the maximum damage to onion stemphiliosis was observed in 2021, which was characterised by high humidity, heavy precipitation, and elevated air temperature. These results are consistent with previous experiments conducted by various authors using onion cultures (Wang et al, 2021;Wright et al, 2019). Gossen et al (2021) identified that the first symptoms of onion stemphiliosis coincided with the appearance of a large number of conidia, precipitation, leaf moisture duration of ≥8 hours, and days with an average daily temperature of ≥18°C.…”
Section: Source: Mycobank Database 2022supporting
confidence: 92%
“…Pathogenic fungal strains, Colletotrichum spaethianum strain SX15-2 and Stemphylium vesicarium strain SX20-2, were isolated during our previous studies from infected Welsh onion plants with leaf blight symptoms [ 6 ]. For inoculation experiments, the healthy and mature Welsh onion seedlings (70–90 days after planting) were obtained from Welsh onion fields in Wan-Fu Village, Sanxing, Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…Control plates were prepared with only the pathogen. The inhibition rate of mycelial growth (IRM) was evaluated using the formula below [ 6 ]: IRM (%) = (Control colony diameter − Treatment colony diameter/Control colony diameter) × 100% …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations